Aortic Valvular Heart Disease in the Adults - Ortega-Gil, Jorge; Rodríguez-Castro, José M. (Puerto Rico Health Sciences Journal, 2009)
Valvular Heart Disease (VHD) is an important cardiovascular problem in the adult population. The knowledge of the physiology involved, prompt recognition and diagnosis are of paramount importance for the primary care physician who is in the front line of patient care. This article is the second of a series of two that deals with valvular problems in the adults in concise and practical form (11). Each topic will be presented using the following format: description, etiology, pathophysiology, natural history, essential of diagnosis and management. In this second and final article we will discuss aortic valve disorders.